2005
DOI: 10.1128/aem.71.10.6254-6259.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine Nucleoside Salvage Confers an Advantage to Xenorhabdus nematophila in Its Host Interactions

Abstract: Xenorhabdus nematophila is a mutualist of entomopathogenic nematodes and a pathogen of insects. To begin to examine the role of pyrimidine salvage in nutrient exchange between X. nematophila and its hosts, we identified and mutated an X. nematophila tdk homologue. X. nematophila tdk mutant strains had reduced virulence toward Manduca sexta insects and a competitive defect for nematode colonization in plate-based assays. Provision of a wild-type tdk allele in trans corrected the defects of the mutant strain. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The data presented here expand the understanding of which metabolic pathways are important for the establishment of colonization. Earlier analyses Orchard and Goodrich-Blair, 2005) had indicated that X. nematophila folate biosynthesis (defective in pabA and aroA mutants) is necessary for normal colonization. There are numerous folate-dependent biosynthetic pathways in bacteria, but it was suggested that folate-dependent methionine biosynthesis in particular might be necessary for eYcient colonization.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here expand the understanding of which metabolic pathways are important for the establishment of colonization. Earlier analyses Orchard and Goodrich-Blair, 2005) had indicated that X. nematophila folate biosynthesis (defective in pabA and aroA mutants) is necessary for normal colonization. There are numerous folate-dependent biosynthetic pathways in bacteria, but it was suggested that folate-dependent methionine biosynthesis in particular might be necessary for eYcient colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures were grown in a tube roller at 30°C in Luria-Bertani (LB) broth [11] except for the FUdR growth assays, which were performed in semi-defined medium containing 5-fluorodeoxyuridine ([12]; FUdR obtained from Fisher Scientific, Pittsburgh, PA) at 37°C with shaking in a microplate reader (Molecular Devices, Sunnyvale, CA) as described previously [3]. LB agar (20 g l -1 ) plates and all liquid media were supplemented when appropriate with kanamycin (kan; 20 μg ml -1 ), chloramphenicol (cam; 20 μg ml -1 ), isopropyl-β-D-thiogalactopyranoside (IPTG; 0.2 mM) or arabinose (0.2%).…”
Section: Methodsmentioning
confidence: 99%
“…The predicted Xenorhabdus nematophila Tdk protein is 70% identical to E. coli Tdk and has been shown to have deoxythymidine kinase activity [3], converting salvaged deoxythymidine to deoxythymidine monophosphate [4]. A translational start site was predicted for X. nematophila tdk based on alignment with tdk sequences from other organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Unless otherwise indicated, all DNA procedures followed standard protocols and specific recommendations from manufacturers. E. coli knockout mutants were constructed by the suicide vector method (16). E. coli genes were amplified from genomic DNA by using AccuPrime Pfx DNA polymerase (Life Technologies, Invitrogen) and cloned into vectors by using the Quick Ligation kit (New England BioLabs Inc., Ipswich, MA) or In-Fusion HD cloning kit (Clontech Laboratories Inc., Mountain View, CA).…”
Section: Methodsmentioning
confidence: 99%